Multiple ekkrine Hidrozystome an Stirn und Nase eines 60-jährigen Mannes - Winkler, Julia K.; Hartschuh, Wolfgang; Enk, Alexander; Toberer, Ferdinand (Der Hautarzt, 2017)
Multiple eccrine hidrocystomas are benign cystic skin lesions which originate from the sweat gland ducts and typically affect women’s midfacial area. Sweating may lead to an increase in size of the translucent papules. In some cases hidrocystomas are associated with other diseases such as Parkinson’s disease. Treatment options include laser, topical and systemic anticholinergic drugs (glycopyrrolate, clonidine, atropine, and oxybutynin), whereby therapeutic success is limited in most cases.